The color of the skin. 2. Hypermelanosis Nevic disorders. Acquired hypermelanosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Early hypermelanosis may be inherited - these lesions were treated in the European Journal of Pediatric Dermatology n. 2, 1993 - or nevic. The latter may be due to increased number of nevus cells at the dermoepidermal junction (lentigo), of melanocytes in the deep dermis (dermal melanocytosis) and of only melanin (hyperpigmented nevus). Nevic hypermelanosis manifests itself with not infiltrated dark patches and due to this characteristic it is treated in this chapter, from which common nevus cell nevi are excluded due to the fact that they are often raised or infiltrated. (...).